INTEGRATED IDENTITY AND ACCESS MANAGEMENT SYSTEM FOR TERTIARY INSTITUTIONS IN DEVELOPING COUNTRIES (Nigerian Journal of Technology, 2015)
Issuance of disparate identifiers to students, manual method of student identity management and access control and the unavailability of actionable information on pattern of students’ use of schools’ services describe identity and access management in tertiary institutions in developing countries. An Integrated Identity and Access Management System for tertiary institutions is developed in this work. This Tertiary Identity and Access Management System (T-IAMS) is a fingerprint biometric database that centrally manages students’ identity, course registration, library and medical services information.  It shortens student provisioning and de-provisioning processes, provides medical service data mining functionality and offers examination screening module which checks students into examination centres by cross-referencing database enrolment with course registration status. The system was developed following exploratory type of evolutionary software development model. MySql was used in building the database and Visual Basic for developing the graphic user interface of the student record module. The work also reports the results of testing done by 20 testers, on a 5-point scale. Analysis of the test results shows the system’s average acceptability percentage of 100 in ability to prevent duplicate enrolments, 79.165 in effectiveness in student clearance while the format and usefulness of reports generated on the medical service module recorded 73.125 as average acceptability percentage. Also, effectiveness in examination screening averaged 66.785 in performance acceptability. It has been shown that managing student identity centrally eases student provisioning and de-provisioning processes, and tightens access control to school facilities and programmes. http://dx.doi.org/10.4314/njt.v34i4.23